Penerapan Metode Diskusi pada Mata Pelajaran PAI Terhadap Motivasi Belajar Siswa - Muhammad Imam Syafi'i; Jumaidah Jumaidah (JURNAL ILMU PENDIDIKAN & SOSIAL (SINOVA), 2023)
Student motivation has little effect on students' understanding of Islamic religious education subject matter and the success rate of teachers' teaching. Likewise with the accuracy of the selection of learning methods used by the teacher. This study aims to increase student motivation by applying the discussion method to Islamic religious education learning materials. The method used in this research is a class action research method. The location of the research was conducted at DDI North Sangatta Islamic Middle School. The results showed a significant increase after the action was taken with an average daily score of 88.6, a daily test score of 86.6, a practice score of 84.5, and a portfolio score of 87.7. This improvement is inseparable from changes in the methods used in the learning process, where previously the teacher's actions used the lecture method.